Forgotten Voices: The Onerous Role of School Health Nurses Residential Schools of India- A View Point - Dhakshayani T., Dhakshayani (Chakra Brahmanda Lentera Institute, 2023)
Background: School health nursing is a specialized practice that addresses students' well-being. Apart from routine health screening, immunization, and health education, the role of school health nurses is expanding to deal with public health crises. remains a challenging concept to practice school health nursing. This article reflects on the challenges of school health nurses and methods to overcome these challenges at different levels- Individual, Professional, Organizational, and Policymaking Methods: Continuing professional education is the best way to manage school health nursing challenges. Upgradation of knowledge and skills can offer new career opportunities. The following are the methods to overcome the challenges discussed above. Results: Discrepancies in guidelines and protocols and lack of written standing orders for school health practice reflect inconsistent and incompatible expectations and demands at work. Information deficits concerning which tasks and responsibilities individuals should undertake have been shown to result in work stress. Policies and protocols exist but not in reality. Policies, protocols, annual performance appraisal records, and training schedules exist for school health nurses but not in reality and practice Conclusion: In residential schools, the school nurse is often the only healthcare professional to meet the students and staff's routine and emergency needs. The work of school nurses is essential in supporting children to have a whole, active, and healthy school life. With such an important role, adequate school nurses must be recruited and provided with the necessary power and infrastructure to ensure their positive contribution to student’s health